Understanding the global measurement of willingness to pay in health. Issue 1 (1st January 2020) - McDougall, Jean A.; Furnback, Wesley E.; Wang, Bruce C. M.; Mahlich, Jörg
ABSTRACT: Objective : To understand the different methodologies used to elicit willingness to pay for health and the value of a statistical life year through surveys. Methodology : A systematic review of the literature was undertaken to identify studies using surveys to estimate either willingness to pay for health or the value of a statistical life year. Each study was reviewed and the study setting, sample size, sample description, survey administration (online or face to face), survey methodology, and results were extracted. The results of the studies were then compared to any published national guidelines of cost-effectiveness thresholds to determine their accuracy. Results : Eighteen studies were included in the review with 15 classified as willingness to pay and 3 value of a statistical life. The included studies covered Asia (n = 6), Europe (n = 4), the Middle East (n = 1), and North America (n = 5), with one study taking a global perspective. There were substantial differences in both the methodologies and the estimates of both willingness to pay and value of a statistical life between the different studies. Conclusion : Different methods used to elicit willingness to pay and the value of a statistical life year resulted in a wide range of estimates.